Hippocampal Volumes and the BDNF val66met Polymorphism in Geriatric Major Depression - Kanellopoulos, Dora (2011)
OBJECTIVES: Structural abnormalities in the hippocampus have been implicated in the pathophysiology of major depressive disorder (MDD). The brain derived neurotrophic factor (BDNF) val66met polymorphism may contribute to these abnormalities and therefore confer vulnerability to MDD. This study examined whether there is a relationship among BDNF genotype, hippocampal volumes, and MDD in older adults. METHODS: Thirty-three older adults with MDD and 23 psychiatrically normal comparison subjects were studied. Structural MRI analysis was used to quantify hippocampal volumes. A repeated measures ANCOVA examined the relationships among BDNF val66met (val/val, met carrier), diagnosis (depressed, non-depressed), and hippocampal volumes (right, left). Age, gender, education, and whole brain volume were included as covariates. RESULTS: Elderly MDD BDNF val/val homozygotes had significantly higher right hippocampal volumes compared with non-depressed val/val subjects. However, there was no difference between the depressed and healthy non-depressed met carriers. Additionally, depressed met carriers had an earlier age of onset of depressive illness than val/val homozygotes but age of onset did not moderate the relationship between hippocampal volumes and MDD diagnosis. CONCLUSION: These results provide preliminary evidence of a neuroprotective role of the val/val genotype, suggesting neurotrophic factor production protects against pathophysiological processes triggered by depression in older adults with later age of onset of MDD. The BDNF val66met polymorphism may play a salient role in structural alterations of the hippocampus in older adults with MDD.